The influence of physical activity on the emotional and moral qualities of students - Grigan S.A.; Romanchenko S.A. (Theory and Practice of Physical Culture, 2025)
Sport is not only physical activity, but also an opportunity for self-development. Physical education strengthens personal qualities and helps to overcome difficulties. Also, sport forms such important qualities as honesty and respect not only for oneself, but also for the opponent. Physical education and sport not only help students to be healthy, but also form our personality, attitude to life, the importance of balance between mental and physical development. Sport develops determination and self-control, which affect many aspects of life. The purpose of the study was to determine the impact of physical activity on the emotional and moral qualities of students. The group of respondents consisted of 100 students of 1-3 courses of PGUPS. Regular exercise helps develop fairness, integrity, and respect for others. In addition, sports help develop discipline and self-discipline, which is important for success in both academic and professional life. Active participation of students in sports events helps them respect rules, be tolerant, and recognize diversity. Sports also strengthen moral fortitude and a sense of responsibility, which is important for a mature personality. Sports can also develop leadership skills and the ability to work in a team. It teaches decision-making and being honest and open to both oneself and others. To summarize, physical education and sports have a complex effect on the development of students’ moral and ethical qualities, which ultimately contributes to their personal growth and the formation of social skills.